(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Religion, National Identity, and the Politics of Georgia.On October 17th, 1999, sixty Jehovah’s Witnesses were attacked by a mob of Georgian religious nationalists. The leader of the mob, defrocked priest Basil Mkalavishvili, later stated that he had acted “in defense of Georgia” by attacking those that he believed to be “traitors to the motherland” for their “abandonment” of the Georgian Orthodox Church. As the police, the judiciary, the government, the church, and a fair number of ordinary people turned a blind eye – or outright lent their support to Mkalavishvili – in the following weeks, it became clear that many Georgians at least tacitly believed that what he was doing was right. This was not an isolated expression of hate. Many other acts of violence followed, targeting more Jehovah’s Witnesses and members of other minority groups in Georgia. Some people – like Malkhaz Songulashvili of the Evangelical Baptist Church of Georgia – argue that people like Mkalavishvili and his associates were only “small fries” who “carried out [these] attacks on the orders of others.” Allowing the public view of religious violence to remain fixed on people like Mkalashvili would leave them with the idea that it was only those who carried out the attacks who were responsible – thus neglecting the importance of other individuals and institutions. While studying individuals and institutions can help us better understand this intolerance, I believe that it cannot be fully grasped without acknowledging its deeper roots. I argue, therefore, that a particular vision of Georgian national identity – constructed around Orthodox Christianity – has animated the politics of Georgia since its independence, motivating exclusionary policies at best and violent religious nationalism at worst. Political leaders have consistently drawn upon narratives of Georgian nationhood, power, and prestige being tied to Orthodox Christianity and have looked to the Georgian Orthodox Church to legitimize their regimes. This paper, therefore, examines how and why religion has been centered in Georgian identity discourse, and its impact on politics.